Effetto del consumo di fragole sullo status antiossidante di soggetti sani - Tulipani, S.; Romandini, S.; Alvarez Suarez, J.; Battino, et al., M. (Progress in Nutrition, 2010)
Riassunto Numerosi studi epidemiologici confermano la correlazione tra un alto consumo di frutta e verdura e una ridotta incidenza di numerose patologie croniche. Negli ultimi anni è emerso il crescente interesse sui potenziali effetti benefici legati al consumo di fragola (Fragaria x ananassa, Duch.), che insieme ad altri piccoli frutti a bacca rossa possiede un alto contenuto di sostanze ad azione antiossidante, sia micronutrienti che composti fitochimici. Nel nostro studio abbiamo valutato l’effetto di un consumo acuto e prolungato di fragole sui principali biomarcatori dello status antiossidante, in soggetti sani. Nel corso della sperimentazione, sono stati valutati gli eventuali cambiamenti nella capacità antiossidante totale plasmatica, nei livelli serici dei principali antiossidanti idrofilici e lipofilici, e nella resistenza della membrana eritrocitaria a uno stimolo ossidativo di diversa intensità, indotto ex vivo. I risultati preliminari ottenuti con questo lavoro suggeriscono la necessità di ulteriori approfondimenti sul possibile impatto del consumo di fragole sulla salute umana. Studi in vivo focalizzati su soggetti iperuremici e con carenze accertate di folato sono inoltre fortemente auspicati. Strawberry consumption and antioxidant status in healthy human subjects Summary A growing body of epidemiological studies suggests a consistent association between the consumption of diets rich in fruits and vegetables and a lower incidence of several chronic diseases. Strawberry (Fragaria x ananassa, Duch.) is among the most popularly consumed berries, both in fresh and processed forms, and its nutritional value has been exhaustively proved1 and correlated to the high content of micronutrients (vitamin C, folate) and the relevant concentration and variety of phenolic constituents. For these reasons, the impact of strawberry consumption on human health is currently receiving ample attention. However, the majority of the scientific research is still focused to obtain in vitro instead of in vivo evidence of the potential bioactivities of strawberry. In our work, to the phytochemical and nutritional characterization of strawberry fruits2 we combined the evaluation of the effects of strawberry consumption on human subjects, by evaluating both plasma and cellular markers of antioxidant status. Sequential feeding studies were carried out, inviting volunteers to an acute and prolonged consumption of relevant amount of strawberries. The potential changes in the plasma TAC, in the concentrations of the main hydrophilic and lipophilic serum antioxidants, and in blood cells resistance to induced oxidative stress were measured. The preliminary results obtained in this work suggest that further investigations on the impact of strawberry on human health and disease are required, and future specific dietary studies in human subjects are strongly hoped.